Population-based projections of blood supply and demand, China, 2017–2036 - Yu, Xiaochu (Bull World Health Organ, 2020)
OBJECTIVE: To estimate the long-term effect of the changing demography in China on blood supply and demand. METHODS: We developed a predictive model to estimate blood supply and demand during 2017–2036 in mainland China and in 31 province-level regions. Model parameters were obtained from World Population Prospects, China statistical yearbook 2016, China’s report on blood safety and records from a large tertiary hospital. Our main assumptions were stable age-specific per capita blood supply and demand over time. FINDINGS: We estimated that the change in demographic structure between 2016 (baseline year) and 2036 would result in a 16.0% decrease in blood supply (from 43.2 million units of 200 mL to 36.3 million units) and a 33.1% increase in demand (from 43.2 million units to 57.5 million units). In 2036, there would be an estimated shortage of 21.2 million units. An annual increase in supply between 0.9% and 1.8% is required to maintain a balance in blood supply and demand. This increase is not enough for every region as regional differences will increase, e.g. a blood demand/supply ratio ≥ 1.45 by 2036 is predicted in regions with large populations older than 65 years. Sensitivity analyses showed that increasing donations by 4.0% annually by people aged 18–34 years or decreasing the overall blood discard rate from 5.0% to 2.0% would not offset but help reduce the blood shortage. CONCLUSION: Multidimensional strategies and tailored, coordinated actions are needed to deal with growing pressures on blood services because of China’s ageing population.